Rocking the boat: does perfect rowing crew synchronization reduce detrimental boat movements? - Cuijpers, L. S.; Passos, P. J. M.; Murgia, A.; Hoogerheide, A.; Lemmink, K. A. P. M.; de Poel, H. J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
In crew rowing, crew members need to mutually synchronize their movements to achieve optimal crew performance. Intuitively, poor crew coordination is often deemed to involve additional boat movements such as surge velocity fluctuations, heave, pitch, and roll, which would imply lower efficiency (eg, due to increased hydrodynamic drag). The aim of this study was to investigate this alleged relation between crew coordination and boat movements at different stroke rates. Fifteen crews of two rowers rowed in a double scull (ie, a two-person boat) at 18, 22, 26, 30, and 34 strokes per minute. Oar angles (using potentiometers) and movements of the boat (using a three-axial accelerometer-gyroscope sensor) were measured (200 Hz). Results indicated that crew synchronization became more consistent with stroke rate, while surge, heave, and pitch fluctuations increased. Further, within each stroke rate condition, better crew synchronization was related to less roll of the boat, but increased fluctuations regarding surge, heave, and pitch. Together this demonstrates that while better crew synchronization relates to enhanced lateral stability of the boat, it inevitably involves more detrimental boat movements and hence involves lower biomechanical efficiency.